ISOLATED HYDATID DISEASE OF THE ILIAC BONE - Mazloum Farsi Baf, Morteza; Mazloum Farsi Baf, Mostafa; Sasannejad, Payman (Journal of Ayub Medical College Abbottabad, 2015)
Hydatid disease of the bone usually is asymptomatic and is found as an accidental finding during unrelated imaging. However, they can become symptomatic due to enlargement and pressure effect or being infected by bacteria. Hydatid disease usually involves multiple organs (such as liver, lungs and brain). In our case, hydatid disease had involved bone and the patient presented only with a chronic hip pain without other symptom or sign. Here, a case of isolated ilium hydatidosis is reported.